2022
DOI: 10.3390/healthcare10102008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Strategies for Managing Stress by Polish Nurses during the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic is having a negative impact on the mental health of nurses around the world. The aim of the study was to assess the sense of fear and the degree of exposure to SARS-CoV-2 infection and to estimate the influence of various factors on the fear of SARS-CoV-2. We analysed methods and strategies for coping with stress used by Polish nurses during the COVID-19 pandemic. Methods: The study was conducted using a diagnostic survey, which included a self-constructed questionnaire and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, contrary to the results obtained in our study, other studies by Polish researchers indicate that more medics used adaptive strategies of coping with stress [ 45 ]. For example, a study conducted in a group of Polish nurses showed that they prefer active strategies for coping with stress and focus on the problem, while they least often resort to psychoactive substances [ 46 , 47 ] or cease activities [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to the results obtained in our study, other studies by Polish researchers indicate that more medics used adaptive strategies of coping with stress [ 45 ]. For example, a study conducted in a group of Polish nurses showed that they prefer active strategies for coping with stress and focus on the problem, while they least often resort to psychoactive substances [ 46 , 47 ] or cease activities [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Stefanowicz-Bielska et.al., most nurses responded that they have often or almost always been concentrating their efforts on doing something about the situation they are in (45% and 42%, respectively) and they have been taking action to try to make the situation better (37% and 51%, respectively). The majority of nurses stated that they never take the following action: I’ve been saying to myself “this isn’t real” (48%), I’ve been using alcohol or other substances to make myself feel better (72%), I’ve been using alcohol or other drugs to help me get through it (75%), and I’ve given up the attempt to cope (51%) [ 33 ]. Analysing the impact of education in the presented work, we notice that staff with a diploma (1.69) and a master’s degree (1.7), more often than people with a bachelor’s degree (1.46), during difficult life situations deal with other activities in order not to think about the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Participants of this study also participated in a study about strategies for managing stress [ 26 ].…”
Section: Methodsmentioning
confidence: 99%